Analisa Keandalan Operator Mesin Giling CTC Pada Produksi Teh Kebun Wonosari - Faisyah Rizky Hidayati; Endang Pudji W (Jurnal Kendali Teknik dan Sains, 2023)
Tea is a plantation commodity that is in great demand and needed. Day by day, there are more connoisseurs and requests regarding the types and forms of tea. In the process, tea processing requires expertise in processing each quality. The purpose of this study is to identify what factors influence human error during the milling process, find out the type of work that gets the highest HEP value, and provide suggestions for improvements to reduce human errors that occur in the processing process. This research was conducted at the Wonosari Tea Plantation Factory. From the results of observations, it was obtained that the largest human error probability was obtained at the Wonosari Garden Tea Factory in the milling process with a probability of 0.7997584. And the lowest HEP is on the task of maintaining a max temperature of 27oC with a value of 0.00000681. The thing that is proposed to the company to reduce the human error that occurs is to provide an understanding of the SOP and emphasize the SOP that applies to the processing process. Companies can also use the HEP value as a reference to reduce human error that can harm the company.